Impact of Professional Competence, Motivation and Work Discipline on Teacher Performance - Rahmayanti, Rahmayanti; Haryati, Titik; Miyono, Noor (Economic Education Analysis Journal, 2021)
This study aimed to analyze the effect of professional competence, work motivation, and work discipline on teacher performance of State Senior High School in Pemalang Regency, either partially or simultaneously. This research was included in ex-post facto research and was quantitative in nature. The population were civil servant teachers which consisted of 10 State Senior High Schools in Pemalang Regency. Proportional simple random sampling was the sampling technique used in this study. Total of samples in this study were 200 samples. The technique of collecting data used a questionnaire. The results showed that the percentage of influence of professional competence, work motivation and work discipline on teacher performance of State Senior High School in Pemalang Regency was 57.7%, the rest were affected by other variables outside the research. The first hypothesis (H1), the second hypothesis (H2), and the third hypothesis (H3) which is that professional competence, work motivation, work discipline have a positive effect on teacher performance of state senior high school throughout Pemalang Regency were partially accepted.